2021
DOI: 10.1016/j.eclinm.2021.101063
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health crisis during waves one and two of the COVID-19 pandemic in India: Incidence and deaths from severe maternal complications in more than 202,000 hospital births

Abstract: Background: The SARS-CoV-2 pandemic in India has adversely affected many aspects of population health. We need detailed evidence of the impact on reproductive health in India so that lessons can be learnt. Methods: Hospital-based repeated monthly survey of nine severe maternal complications and death in 15 hospitals across five states in India covering a total of 202,986 hospital births, December-2018 through to May-2021. We calculated incidence rates (with 95% confidence intervals (CIs)) per 1000 hospital bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…3 4 Currently, there is evidence that women diagnosed with COVID-19 have higher risk of eclampsia/pre-eclampsia, maternal mortality, stillbirth, preterm birth and congenital birth defects. [5][6][7][8][9] A multinational cohort study showed that delivery by caesarean section, but not breastfeeding, was associated with an increased risk of SARS-CoV-2 transmission to newborns. 8 The WHO recommends that for women confirmed with COVID-19, labour induction and caesarean section should only be undertaken when medically indicated, and that breastfeeding should be encouraged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 4 Currently, there is evidence that women diagnosed with COVID-19 have higher risk of eclampsia/pre-eclampsia, maternal mortality, stillbirth, preterm birth and congenital birth defects. [5][6][7][8][9] A multinational cohort study showed that delivery by caesarean section, but not breastfeeding, was associated with an increased risk of SARS-CoV-2 transmission to newborns. 8 The WHO recommends that for women confirmed with COVID-19, labour induction and caesarean section should only be undertaken when medically indicated, and that breastfeeding should be encouraged.…”
Section: Introductionmentioning
confidence: 99%
“…This uncertainty was accompanied by reorganisation of care provision models and introduction of mitigation measures that were not supported by evidence, such as separation of mothers confirmed with COVID-19 from newborns and not allowing breastfeeding 3 4. Currently, there is evidence that women diagnosed with COVID-19 have higher risk of eclampsia/pre-eclampsia, maternal mortality, stillbirth, preterm birth and congenital birth defects 5–9. A multinational cohort study showed that delivery by caesarean section, but not breastfeeding, was associated with an increased risk of SARS-CoV-2 transmission to newborns 8.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we observed a statistically significant increase in maternal mortality (1.5% vs 13.7%; p<0.001) and noted ARDS and DIC as the most common cause of death. Mahajan et al reported pneumonia and respiratory failure as the most common causes of maternal mortality [ 8 ]; while Nair et al attributed the increase in overall case fatality rate to reduced hospital visits and reduced hospital births rather than the COVID-19 infection directly [ 3 ]. Contrary to our findings studies from Spain reported better outcomes in the second wave with a lower case fatality rate (24.0% vs 13.2%) which was attributed to more experience, availability of more effective therapeutic interventions and probably to a new variant of concern (VOC) 20A.EU1 [ 10 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, 22.7% increase in maternal mortality, 4.8% increase in neonatal mortality and 3.4% increase in perinatal mortality have been reported [ 2 ]. India has also experienced 23% increase instead of 5.5% annual decline in maternal mortality ratio during a pandemic, which should draw urgent attention of policymakers [ 3 , 4 ]. The disproportionate impact of pandemic on maternal and perinatal outcome has surfaced in two waves worldwide as well as between high-income countries and low-middle income countries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Los ingresos hospitalarios por aborto séptico fueron un 56% más elevados (RR=1,56), la letalidad global de las complicaciones aumentó un 23% (RR=1,23, p = 0,022) y se mantuvo elevada en las distintas fases de la pandemia, con notable aumento significativo de las muertes por insuficiencia cardíaca en el embarazo. Este estudio apoya la legitimidad de los llamamientos realizados para mantener los servicios de salud sexual y reproductiva como servicios esenciales durante la pandemia (60) .…”
Section: Problemas Encontradosunclassified